Transformation of archetypes in the works of John Tolkien - Muzaffarov, Javlon (The Lingua Spectrum, 2025)
This article analyzes the interrelation of the landscape of space and time in works of art. Artistic space is a reflection of the author’s unique views, imaginations and aesthetic position about the world. It manifests itself in various forms and directions, and in close connection with social, moral and cultural factors, it acquires a semantic load in the artistic text.